2021
DOI: 10.1108/mip-05-2021-0164
|View full text |Cite
|
Sign up to set email alerts
|

Social media marketing, shoppers' store love and loyalty

Abstract: PurposeThis study investigates the impact of social media marketing activities (SMMA) on shoppers' store love and the impact of store love on store loyalty in grocery retail. Moreover, it explores the mediating and moderating role of store love and social media usage intensity (SMUI).Design/methodology/approachA survey was conducted among grocery shoppers and social media users in Norway. A total of 177 valid responses were collected and analyzed using partial least squares structural equation modeling (PLS-SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Furthermore, SMMAs play a "considerable role in building trust and the consumer-brand relationship, which lead to positive business outcomes in turn" (Cheung et al, 2020a, b and c, p. 698). Many scholars have suggested that various effects can flow from SMMAs, such as trust, purchase intention, customer engagement and loyalty (Ahmed, 2021;Khan, 2022). In the context tourism and leisure industry, identified a positive link between SMMAs and customers' intentions to revisit for coffee shop brands through the sequential mediation of brand trust and loyalty.…”
Section: Smmasmentioning
confidence: 99%
“…Furthermore, SMMAs play a "considerable role in building trust and the consumer-brand relationship, which lead to positive business outcomes in turn" (Cheung et al, 2020a, b and c, p. 698). Many scholars have suggested that various effects can flow from SMMAs, such as trust, purchase intention, customer engagement and loyalty (Ahmed, 2021;Khan, 2022). In the context tourism and leisure industry, identified a positive link between SMMAs and customers' intentions to revisit for coffee shop brands through the sequential mediation of brand trust and loyalty.…”
Section: Smmasmentioning
confidence: 99%
“…According to Cheung et al, (2020) these two way communication can facilitate customers to understading the brand's value and lead the bonding between brands and customers [12,19].…”
Section: Interactivitymentioning
confidence: 99%
“…Furthermore, big and small businesses create brand pages through SNSs for their products and services and to spread information to their many current and potential customers; these efforts are considered part of a marketing strategy called social media marketing (SMM; Ibrahim, 2021a). SMM is a newgeneration marketing tool that promotes products, services, and ideas and builds brands (Ahmed, 2021;Ibrahim et al, 2022). SMM supports businesses' marketing plans by focusing on interactive relationships with current and new brand consumers (Upadhyay et al, 2022) and creating confident exchanges with them (Kumar et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The origin model of SMMAs was explored in the context of the Korean fashion industry (Kim & Ko, 2012). SMMAs are a generally recognized concept that is a subgroup of SMM through SNSs (Ahmed, 2021). A secondary purpose of this study is to examine the mediating influence of members' active participation in the path from SMMAs to IFA, and a third is to examine the mediating effect of benevolence trust on the SMMAs-IFA relationship.…”
Section: Introductionmentioning
confidence: 99%